Multimodal Logistics for Resilient and Sustainable Global Supply Chains: Strategic Insights from Integrated Transport Systems - Kurniawan, Deri Alan (Sinergi International Journal of Logistics, 2024)
Multimodal transportation has emerged as a critical solution for enhancing the efficiency and resilience of integrated logistics networks. This narrative review aims to synthesize current research on the effectiveness of multimodal logistics in addressing global supply chain challenges. Using a structured keyword-based search across Scopus, Web of Science, and Google Scholar, this study selected peer-reviewed literature published between 2010 and 2024. Emphasis was placed on studies focusing on cost optimization, environmental impact, digital integration, and strategic network planning. The review identifies five key dimensions—logistics cost-efficiency, crisis resilience, environmental sustainability, technological integration, and network design—as central to the performance of multimodal systems. Optimization models significantly reduce logistics costs and emissions, while real-time data and IoT systems enhance operational coordination. In crisis contexts, multimodal approaches offer adaptable responses, particularly when supported by digital infrastructure. However, challenges such as regulatory fragmentation and infrastructure disparity limit broader implementation, especially in developing regions. Synchromodal strategies and policy alignment are highlighted as critical enablers of system responsiveness and sustainability. This review concludes that strategic technological and institutional reforms are essential to unlock the full potential of multimodal logistics. Future research should explore adaptive AI-driven models and conduct cross-regional analyses to inform context-specific solutions. Strengthening digital infrastructure and fostering stakeholder collaboration will be key in developing resilient and future-ready logistics systems.